AGW 612 — Corporate Strategy - February 2000 - PPP, Pusat Pengajian Pengurusan (2000)
UNIVERSITI SAINS MALAYSIA MASTER OF BUSINESS ADMINISTRATION Second Semester Examination Academic Session 1999/2000 February 2000 AGW 612 — Corporate Strategy Time: [3 hours]